Black box modelling and simulating the dynamic indoor air temperature of a laboratory using autoregressive–moving-average (ARMA) model - S. F. M. Hussein; N. B. Sharifmuddin; A. O. Al rabeei; A. Faruq; M. S. Noorazizi; S. A. Zaki; SS Abdullah (Institute of Advanced Engineering and Science, 2021)
Mathematical model representing the dynamic indoor air temperature of a building is important for reducing the time and cost required to test any proposed thermal comfort control algorithm and strategy for that building through computer simulation. There are many types of mathematical model, and each type has its strength(s) and weakness(es). An autoregressive–moving-average (ARMA) model, a type of black box model is used to represent the dynamic indoor air temperature behaviour of industrial instrumentation laboratory at malaysia-japan international institute of technology (MJIIT), universiti teknologi malaysia (UTM) Kuala Lumpur based on the recorded data from the laboratory and minimal physical characteristics knowledge of the laboratory. The ARMA model’s output developed in this research is compared with the actual data recorded from the laboratory for performance measurement. The obtained result shows that the ARMA model is sufficient for modelling and simulating the dynamic indoor air temperature behaviour of the laboratory.